Data Handling : Across the Curriculum Year 3 - Montague-Smith, Ann (Leamington Spa Scholastic, 2011)
The Teachers' Book and acompanying CD-ROM has over twenty full lessons which cover history; citizenship; science; PE; geography; design & technology; ICT; music; art & design; and English
Include Illustrations and CD
Keywords: Mathematics--Study and teaching (Elementary)--Activity programs -- Great Britain -- Interdisciplinary approach in education